Ahmed Gaid Salah: The Algerian Lincoln - Youcef TOUFOUTI (Akofena, 2022)
Just as Abraham Lincoln is placed as the greatest American president ever, Algeria’s former chief of staff, Ahmed Gaid Salah who died in 2019, is seen by many Algerians as a paragon of patriotism. This article, however, strips away the mask of grandeur to reveal the profound truths of the controversial men underneath. It also suggests that they share striking similarities in dealing with themes of power, war, and death. Despite their poor backgrounds, they saw themselves as grander and loftier. Truly, they were not cultivated, yet they understood the world of self-interest and ambition. As America plunged into Civil War, Lincoln pragmatically emancipated slaves to restore the Union. Similarly, Gaid seized the opportunity of Hirak to turf out president Bouteflika and become the most powerful man in Algeria. Most importantly, both take part of the blame for the astounding numbers of dead people in the American and Algerian Civil Wars. Finally, the timing of their death was perfect. While Lincoln died triumphant only a few days after winning the Civil War, Gaid too died in a moment of victory, barely a week after a presidential election that he strongly pushed for. Undoubtedly, it is the timing of their death that led to the creation of two legends that still obscure their true personalities. This article aims to show that Lincoln’s and Gaid Salah’s place in history is intentionally elevated to a mythical position despite the fact that they were rife with contradictions.